Perfectly Competitive Markets in Islamic Economics: A Systematic Literature Review on Efficiency, Justice and Market Ethics - Junia Mayang Sari; Rozalinda; Testru Hendra (FEBI IAIN Langsa, 2026)
This study aims to analyze the development of research on perfect competition markets from an Islamic economic perspective using a Systematic Literature Review (SLR) approach. Previous research has generally focused more on market efficiency in conventional economics, while the integration of efficiency, justice, and Sharia ethics has been discussed only to a limited extent in a systematic manner. Furthermore, there are still relatively few SLR studies on perfect competition markets in Islamic economics. This study employs the PRISMA method on Scopus-indexed and web of science articles from 2019 to 2025 using the keyword “perfect competition market in Islamic perspective.” From the initial 85 articles identified, a screening process was conducted based on topic relevance, methodological suitability, and eligibility criteria. Consequently, 10 final articles were selected for in-depth analysis. The results indicate that previous studies have been dominated by discussions of market efficiency and price mechanisms, while aspects of market ethics, Sharia oversight, and distributive justice remain relatively under-researched. Furthermore, most studies remain conceptual and normative, with limited empirical research on the implementation of Islamic markets within the context of modern economics. This study underscores the importance of developing Sharia-based market regulations and models that are oriented not only toward economic efficiency but also toward social justice and welfare.